DETERMINANTS OF FINANCIAL TECHNOLOGY (FINTECH) ADOPTION BEHAVIOR IN PERSONAL FINANCIAL MANAGEMENT AMONG ECONOMICS EDUCATION STUDENTS IN EAST JAVA - Kartini, Titin; Sugeng, Bambang; Wahyono, Hari; Wardoyo, Cipto (UNIVERSITAS NEGERI SURABAYA, 2025)
Rapid advancements in technology related to the fourth industrial revolution have transformed the way financial transactions are conducted, shifting from conventional cash methods to digital finance, also known as fintech. Despite this shift, the adoption of fintech is inconsistent, especially among students, who are an important group for promoting financial inclusion and literacy. This study aims to fill the existing gap by investigating the specific elements that influence fintech adoption among Economics Education students in Java, using the Theory of Planned Behavior (TPB) as a framework. An explanatory quantitative investigation involving 350 students from three accredited universities shows that attitudes, social factors, and digital financial literacy play an important role in shaping students' intentions to use fintech. Importantly, digital financial literacy stands out as a crucial element, both directly and indirectly encouraging responsible financial practices and the adoption of fintech. The originality of this research lies in its examination of the relationship between education and the use of fintech, emphasizing the importance of digital financial literacy in influencing students' financial actions in an increasingly digital economy.